Difference in age, growth, and sexual demography of black‐spot tuskfish, Choerodon schoenleinii (Valenciennes, 1839), in two adjacent populations, Ryukyu Archipelago, southern Japan. (30th January 2017) - Akita, Y.; Ebisawa, A.; Hirai, N.; Asami, K.; Ohta, I.; Uehara, M.; Teruya, K.; Yamada, H.; Kobayashi, M.; Sato, T.; Okuzawa, K.
Summary: To better understand the plasticity of life history traits in the blackspot tuskfish, Choerodon schoenleinii (Valenciennes, 1839), the characteristics of the population around the Yaeyama Islands (24°N, 124E) were examined and compared to those around Okinawajima Island (26°N, 128E) that had been investigated in a previous study. Age and growth of the Yaeyama population were examined based on 103 specimens collected at fish markets between 2006 and 2016. Specimens included 83 females (25.2–69.0 cm total length [TL]), and 20 males (43.1–71.8 cm TL). Ages determined from sectioned otoliths ranged from 1–9 for females, and 4–15 for males. Values for von Bertalanffy growth functions were L t  =   74.2 {1−exp[−0.23 ( t  +   0.38)]}, and the growth of the Yaeyama population was significantly faster than that of the previously studied population. Sexual demography of the two populations was compared using body length data on landings measured at the fish markets. In the Yaeyama population, females and males ranged from 24–65 cm TL and 39–75 cm TL, respectively; length at 50% individual sex change size was estimated at 54.7 ± 0.56 cm (±95% C.I.). In contrast, in the Okinawajima population, females and males ranged from 16–65 cm TL and 30–75 cm TL, respectively; meanwhile, 50% sex change size was estimated to be 50.0 ± 0.25 cm. There were thus significant differences in the size at sex change between the two populations. This difference may be related to the difference in population density between the sites.